Communities of parental engagement: new foundations for school leaders' work. Issue 2 (14th March 2016) - Torre, Daniela; Murphy, Joseph
Abstract : The importance of parents to the success of students in schools and to school improvement has long been established and acknowledged by researchers and educators. In this article, we present a fourth–generation model of school–family linkages, one anchored in understandings of schools as communities as opposed to schools as institutions. Our model is based on an analysis and synthesis of the relevant recent empirical evidence. We extend the narrative of school–parent relationships by highlighting 'norms of community' school leaders can cultivate to promote membership, partnership and ownership.